2001
DOI: 10.1093/ptj/81.4.1029
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Combined With Continuous Passive Motion or Slider Board Therapy Compared With Exercise Only: A Randomized Controlled Trial of Patients Following Total Knee Arthroplasty

Abstract: Background and Purpose. The primary purpose of this randomized controlled trial was to determine which method of mobilization-(1) standardized exercises (SE) and continuous passive motion (CPM), (2) SE and slider board (SB) therapy, using an inexpensive, nontechnical device that requires minimal knee active range of motion (ROM), or (3) SE alone-achieved the maximum degree of knee ROM in the first 6 months following primary total knee arthroplasty (TKA). The secondary purpose was to compare health-related qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 28 publications
5
40
0
2
Order By: Relevance
“…Knee ROM, both toward flexion and extension at 3 months postoperatively was lower than the preoperative level. Previous studies have also reported a 5-15° decrease in knee flexion at follow-up during 2-6 months after surgery (28)(29)(30)(35)(36)(37). conservatively treated individuals with oA have been shown to use a smaller knee angle in AdL performance than healthy controls due to pain and stiffness (38)(39).…”
Section: Discussionmentioning
confidence: 92%
“…Knee ROM, both toward flexion and extension at 3 months postoperatively was lower than the preoperative level. Previous studies have also reported a 5-15° decrease in knee flexion at follow-up during 2-6 months after surgery (28)(29)(30)(35)(36)(37). conservatively treated individuals with oA have been shown to use a smaller knee angle in AdL performance than healthy controls due to pain and stiffness (38)(39).…”
Section: Discussionmentioning
confidence: 92%
“…Auch bei den hier eingeschlossenen Studien sollte kritisch hinterfragt werden, welcher gemessene Unterschied in der Flexion oder Extension im Gruppenvergleich als klinisch relevant gilt. MauMoeller et al [12] und Beaupré et al [9] definieren den klinisch relevanten Unterschied ab einer Differenz von 5 °. Diese wird auch in der Studie von Lenssen et al [18], die die Effektivität einer CPM Therapie evaluieren, angegeben.…”
Section: Bewertung Der Studienunclassified
“…Übersicht der Studiencharakteristiken. MauMoeller et al[12] und Beaupré et al[9] zusätzlich Physiotherapie. Die Studien von Friemert et al[10] und Bizzini et al[8] machten diesbezüglich keine Angaben.…”
unclassified
“…The functional challenges that patients face require good balance skills to prevent falls. Although post-operative exercise programs following THA or TKA may vary across various rehabilitation settings, these exercise programs typically emphasize joint range-of-motion (ROM) and muscle strengthening exercises for patients following TKA 13 17 or THA. 18 , 19 Balance component of mobility and physical function is not adequately addressed in these exercise programs.…”
Section: Introductionmentioning
confidence: 99%